2005
DOI: 10.1097/01.ju.0000154891.40110.08
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Followup of Augmentation Enterocystoplasty and Continent Diversion in Patients With Benign Disease

Abstract: AC and urinary diversion provide a safe and effective long-term therapy in patients with refractory neurogenic bladder but stomal problems in patients with continent diversion continue to be a source of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 19 publications
4
49
1
3
Order By: Relevance
“…Many papers reported that augmentation enterocystoplasty provides benefits of urodynamic parameters in patients with neurogenic bladder. 4,5,7 In the present study, postoperative V-UDS showed a significant improvement after the surgery in bladder capacity, bladder compliance and detrusor overactivity. In addition, preoperative VUR were resolved or improved in all, and none had febrile UTI after the augmentation cystoplasty.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Many papers reported that augmentation enterocystoplasty provides benefits of urodynamic parameters in patients with neurogenic bladder. 4,5,7 In the present study, postoperative V-UDS showed a significant improvement after the surgery in bladder capacity, bladder compliance and detrusor overactivity. In addition, preoperative VUR were resolved or improved in all, and none had febrile UTI after the augmentation cystoplasty.…”
Section: Discussionmentioning
confidence: 65%
“…Augmentation enterocystoplasty is a procedure suitable for these MMC patients in whom conservative medical therapies have failed. 4,5 Although many papers revealed excellent clinical results of augmentation enteroplasty in patients with neurogenic bladder refractory to conservative therapies, [4][5][6][7] there have been few studies describing urodynamic results of augmentation enterocystoplasty and long-term satisfaction with bowel and urinary condition at postsurgery. In fact, as augmentation enterocystoplasty involves the incorporation of a bowel segment into the bladder, MMC patients may suffer from unstable bowel function after the surgery despite of a significant improvement of urinary condition such as urinary incontinence and UTI.…”
Section: Introductionmentioning
confidence: 99%
“…verbessert [26,29]. Allerdings muss das Risiko-Nutzen-Verhältnis für den individuellen Patienten vor der Entscheidung zu einer solchen Operation sorgfältig abgewogen werden, da es trotz einer insgesamt geringen Mortalität zu relevanten perioperativen und langzeitlichen Nebenwirkungen/Komplikationen kommen kann [7,24,64,71].…”
Section: Inkontinente Und Kontinente Harnableitungenunclassified
“…Retraction, stomal prolapse, parastomal hernia, and stenosis are the most frequent. Stenosis occurs in up to 33% of patients and is considered one of the major complications [39][40][41][42][43]. Stomal stenosis can result from a combination of factors, including ischemia, fascial contraction, retraction, local skin alterations, and stoma placement [37,39].…”
Section: Surgical Complications and Treatment Optionsmentioning
confidence: 99%